2017
DOI: 10.1038/s41598-017-06611-3
|View full text |Cite
|
Sign up to set email alerts
|

Associations of plasma homocysteine levels with peripheral systolic blood pressure and noninvasive central systolic blood pressure in a community-based Chinese population

Abstract: Previous studies indicated that homocysteine (Hcy) is associated with higher peripheral systolic blood pressure (pSBP). There have been few data on the relationship between Hcy and central SBP (cSBP). A total of 4,364 Chinese subjects from the Shijingshan community in Beijing were included. cSBP and pSBP were measured with an Omron HEM-9000AI device. Subjects were 57.20 ± 8.9 years old, 37.9% were male. The median of Hcy was 11.96 μmol/L. The mean of cSBP and pSBP was 129.94 ± 18.03 mmHg and 133.25 ± 18.58 mmH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…Homocysteine (Hcy) has been involved in the pathogenesis of hypertension by producing endothelial injury [3,4], increasing oxidative stress [5], stimulating the proliferation of vascular smooth muscle cells (VSMCs) [6], and altering the elastic properties of the vascular wall [7]. Elevated Hcy and its related genetic variants have been associated with blood pressure [8][9][10][11][12], hypertension [13][14][15], and related vascular complications, e.g., atherosclerosis [16,17], coronary heart disease [18,19], and stroke [20,21], in humans. In the process of Hcy-induced hypertension, the endothelial injury resulting from Hcy promotes platelet consumption and adherence which stimulates the proliferation of VSMCs through releasing mitogenic factors [22], thereby contributing to atherosclerosis, arterial stiffness, and high blood pressure [23,24] Furthermore, platelet activation has been associated with Hcy [25] but also hypertension [26] in population studies.…”
Section: Introductionmentioning
confidence: 99%
“…Homocysteine (Hcy) has been involved in the pathogenesis of hypertension by producing endothelial injury [3,4], increasing oxidative stress [5], stimulating the proliferation of vascular smooth muscle cells (VSMCs) [6], and altering the elastic properties of the vascular wall [7]. Elevated Hcy and its related genetic variants have been associated with blood pressure [8][9][10][11][12], hypertension [13][14][15], and related vascular complications, e.g., atherosclerosis [16,17], coronary heart disease [18,19], and stroke [20,21], in humans. In the process of Hcy-induced hypertension, the endothelial injury resulting from Hcy promotes platelet consumption and adherence which stimulates the proliferation of VSMCs through releasing mitogenic factors [22], thereby contributing to atherosclerosis, arterial stiffness, and high blood pressure [23,24] Furthermore, platelet activation has been associated with Hcy [25] but also hypertension [26] in population studies.…”
Section: Introductionmentioning
confidence: 99%
“…The principle of the method has been described in detail previously. 26 Other laboratory parameters were measured at baseline using a Roche C8000 Automatic Analyzer (Basel, Switzerland).…”
Section: Blood Sample Collection and Laboratory Methodsmentioning
confidence: 99%
“…15 The mean level of Hcy in our sample was 10.5 µmol/L, which was greater than previously reported among American population in the National Health and Nutrition Examination Survey (7.72 µmol/L) and lower than mean value reported among Chinees population (11.96 µmol/L). 16,17 In the last decade, epidemiological observations have reported that Hcy status is linked to cardiovascular disease and was suggested to be an independent predictor of cardiac death among adults. 18 In the current study, Hcy levels varied significantly between males and females.…”
Section: Multivariate Analysis For Hcy Status and Msmentioning
confidence: 99%